2005
DOI: 10.1080/02786820500442410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Shape on Filtration Processes

Abstract: The influence of particle shape on filtration processes was investigated. Two types of particles, including spherical polystyrene latex (PSL) and iron oxide, and perfect cubes of magnesium oxide, were examined. It was found that the removal efficiency of spherical particles on fibrous filters is very similar for corresponding sizes within the range of 50-300 nm, regardless of the fact that the densities of PSL and iron oxide differ by a factor of five. On the other hand, the removal efficiency of magnesium oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 23 publications
2
46
1
2
Order By: Relevance
“…Studies show that cubic particles provide lower particle removal efficiency than do aerodynamically similar spheres. The contact areas following collisions between the filter surface and spherical particles travelling in divergent directions are the same; however, this area may be different for other particle shapes, which alter particle collection efficiency (Boskovic et al, 2005). Spherical particles may either slide or roll upon collision; however, cubic particles could either slide or tumble, increasing the probability of detachment from the surface (Boskovic et al, 2005).…”
Section: Advances In Nanoparticle Filtration Efficiencymentioning
confidence: 99%
“…Studies show that cubic particles provide lower particle removal efficiency than do aerodynamically similar spheres. The contact areas following collisions between the filter surface and spherical particles travelling in divergent directions are the same; however, this area may be different for other particle shapes, which alter particle collection efficiency (Boskovic et al, 2005). Spherical particles may either slide or roll upon collision; however, cubic particles could either slide or tumble, increasing the probability of detachment from the surface (Boskovic et al, 2005).…”
Section: Advances In Nanoparticle Filtration Efficiencymentioning
confidence: 99%
“…It is reported that A and e ought to be determined experimentally because it is very hard to determine them theoretically. Boskovic et al (2005) showed that the effect of particle motion along the fibre should not be ignored. Their experimental results showed that polystyrene latex (PSL) particles of spherical shape in the size range of 50-300 nm are removed from the gas carrier with significantly higher efficiencies compared to cubic MgO particles in the same size range, even if their densities vary by a factor of 3.6.…”
Section: Introductionmentioning
confidence: 98%
“…The size distribution of individual MgO particles generated by a metal combustion was discussed in [10]. As was reported, cubic MgO particles with the side length of 35 nm represented the maximum number concentration of polydisperse aerosol produced by magnesium combustion.…”
Section: Discussionmentioning
confidence: 96%
“…A difference in filtration efficiency between spherical and nonspherical particle of the same electrical mobility diameter in the size range from 50 to 300 nm was reported by Boskovic et al [10,11]. Lower efficiency of non-spherical (cubic) particle compared to the spherical one was ascribed to some difference in rebound probability during particle motion at the fiber surface right after collision.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation